Penggunaan metode decision tree pada PT. HIS Tour & Travel untuk pembukaan cabang baru - Sofiyatun Sofiyatun; Haryadi Sarjono (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
The purpose of this research is to find out the forecasting of flight ticket sales at PT. HIS Tour & Travel Branch MM 2100 Cibitung. This research method uses forecasting with 7 methods namely Exponential Smoothing, Moving Average, Trend Projection, Addictive Decomposition Average All, Addictive Decomposition Centered Moving Average, Multiplicative Average All and Multiplicative Decomposition Centered Moving Average. This research is supported bya QM For Windows application. The results of this study indicate that the Addictive Decomposition Centered Moving Average method is the best method because it has the smallest MAD and MSE value of 104.76 and 22.897,57 with the results of sales forecasting in the next period which is 1371. This study also uses the Decision Tree method for opening decision new branch, the results obtained are the opening of new branches in the city of Bekasi with an expected value of Rp 280,560,000. Keywords: sales promotion, Forecasting, MAD, MSE, QM For Windows, Decision Tree